2015
DOI: 10.3892/ol.2015.2950
|View full text |Cite
|
Sign up to set email alerts
|

Chemoresistance is associated with Beclin-1 and PTEN expression in epithelial ovarian cancers

Abstract: The aim of the present study was to investigate the protein expression of the autophagy-related genes, BECN1 and PTEN, and the association with drug resistance in epithelial ovarian cancers. In total, 40 patients with pathologically diagnosed epithelial ovarian cancer were divided into a chemotherapy-sensitive group (n=20) and a chemotherapy-resistant group (n=20), according to the results of the pre- or post-operative normative chemotherapy and the post-operative follow-up. The protein expression of the phosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 32 publications
2
25
0
Order By: Relevance
“…The antitumor effect of Beclin1 has been confirmed in many previous studies, and Beclin1 gene deletion has been found in ovarian ( 29 31 ), breast ( 32 , 33 ), prostate ( 34 , 35 ) and other tumors ( 36 39 ). However, the underlying mechanism of this phenomenon remains unclear, which has caused a lot of controversy.…”
Section: Discussionsupporting
confidence: 52%
“…The antitumor effect of Beclin1 has been confirmed in many previous studies, and Beclin1 gene deletion has been found in ovarian ( 29 31 ), breast ( 32 , 33 ), prostate ( 34 , 35 ) and other tumors ( 36 39 ). However, the underlying mechanism of this phenomenon remains unclear, which has caused a lot of controversy.…”
Section: Discussionsupporting
confidence: 52%
“…Anti-apoptotic protein BCL-2 overexpression is the most common mechanism of apoptosis evasion, which has been reported be involved in the resistance of cells in a variety of drugs, including doxorubicin, paclitaxel, etoposide, camptothecin, mitoxantrone and cisplatin25, 26, 27. Several other factors, including aberrant activation of protein kinase B, nuclear factor kappa B (NF- κ B), phosphatase and tensin homolog (PTEN) have also been demonstrated to play an important role in developing drug resistance in various cancer types through interfering apoptosis machinery28, 29, 30 (Fig. 1).…”
Section: Mechanisms Of Multidrug Resistancementioning
confidence: 99%
“…Changes in BECN1 and LC3B expression have been reported as features of the cancer state. Some findings suggest that BECN1 is upregulated in glioma and colorectal cancers, leading to poor prognosis in patients [6567], while others observe a reduction in BECN1 and LC3B expression, leading to the tumor progression in gliomas and other cancer types [34, 6871]. These differences may underscore the complexity of the role of autophagy in cancer progression as well as differences in tissue type and origin [23, 72].…”
Section: Discussionmentioning
confidence: 99%